Ion clusters and ion-water potentials in MD-simulations - Bopp, Ph.A.; Ibuki, K. (Condensed Matter Physics, 2012)
A well known, if little documented, problem in many molecular simulations of aqueous ionic solutions at finite concentrations is that unrealistic cation-cation associations are frequently found. One might suspect a defect in the ion-ion interaction potentials, about which not much is known. However, we show that this phenomenon can also be traced to the fact that, in the pair-potential approximation, the cation-water potentials are too deep compared with the other ones and we investigate this phenomenon in some detail. We then attempt to draw some general conclusions. Добре вiдомою, хоча i мало описаною, проблемою при виконаннi чисельних молекулярних симуляцiй водних iонних розчинiв при скiнченних концентрацiях є почасти нереалiстичнi асоцiацiї типу катiон-катiон. Можна припустити, що причиною цього є дефект iон-iонних потенцiалiв взаємодiї, про який вiдомо достатньо мало. Ми показуємо, що це явище може бути спричинене тим, що при використаннi наближення парної взаємодiї потенцiали катiон-вода є занадто глибокими порiвняно iз iншими. Ми детально дослiджуємо цей ефект у нашiй роботi та намагаємось сформувати певнi загальнi висновки.